Ethical reflections on the use of Generative Artificial Intelligence in the academic sphere: writing and authorship - Delgado, Vitor Rabelo; Sales, Keanu Frota; Abreu, Vinícius Augusto Carvalho de (Anais do Workshop sobre as Implicações da Computação na Sociedade (WICS); 2024: Anais do V Workshop sobre as Implicações da Computação na SociedadeDO - 10.5753/wics.2024.3170, 2024)
Generative Artificial Intelligence (GenAI) is emerging as a promising tool in academic production, offering the potential to help with literature reviews, content creation and idea generation. However, the use of AI raises ethical debates related to authorship, plagiarism and intellectual property. Therefore, regulating the use of AI in the academic sphere is necessary, through a dialog between the academic community, companies and governments that defines guidelines that consider principles such as transparency, justice, equity, responsibility and beneficence. The future of academic production will depend on the integration of AI with human expertise and judgment. Thus, this article is a comprehensive review of the existing literature on Generative Artificial Intelligence, ethics and intellectual property, synthesizing a solid knowledge base for discussing the use of these intelligent mechanisms within academic production.